LA BUROCRACIA INSERTA EN UN ENTORNO DINÁMICO - Huaco Pastor, Enrique (2010)
Peruvian society as elsewhere, public and private sectors are shaped by institutions and companies and many of them in the last century took on the bureaucratic model as a form of organization, and now coexist with other organizational models. Significant economic, social, political and technological developments in recent decades in the world have created the bureaucratic organizational model with its best qualities, has been technically surpassed by other models that are flexible and can cope more efficiently and effectively to new challenges of the local environment, sectoral, national and global dynamics are part of a discontinuous, uncertainty and overly competitive Bureaucratic models in the private sector that the twentieth century, in its boom period drove increasing economies of scale through the self-growth, or through takeovers and mergers, however in the last decades of the last century, fragmented self, articulated organizational forms taking business groups, formed by smaller organizations, autonomous, interdependent and integrated with each other in network., in this way had emerged from the bureaucratic structures, which generally had similar charts typically, pyramidal, formalized by excessive rules and centralization in decision-making. Bureaucratic models in the public sector in several foreign countries, mainly in Europe, incorporating the principle of subsidiarity moving to private sector exploration, production and distribution of goods and rendering services. In Peru, I operate the process of regionalization and decentralization and the devolution process and the creation of new ministries with the consequent growth of government and bureaucratic structures.